Aging as a Normative Phenomenon. Issue 4 (21st March 2017) - SCHEFFLER, SAMUEL
ABSTRACT: Many philosophers have discussed the normative significance of personal relationships. The implicit focus of most of these discussions is on the normative significance of active, ongoing relationships. But, of course, all relationships end eventually. This article focuses on relationships that end through the death of one of the participants. A relationship that has ended in this way can still be a source of reasons for the surviving participant. This represents a different dimension of the normative significance of personal relationships, and it is a dimension that tends to become increasingly salient as one ages. Indeed, aging is in part a normative phenomenon, because it involves significant changes in the kinds of reasons people have. This article explores some of those changes and the distinctive questions to which they give rise.